Modificação anódica de implantes a base de titânio e estudo de sua utilização como plataforma para liberação de fármacos - Simon, Anna Paulla (2019)
Aiming the development of anodic titanium-based biomaterials that presents suitable properties for biomedical application, the surface modification and the enhancement of bacterial activity were explorated this work. Titanium nanotubes (TiNTs) were grown over Ticp (T) and Ti6Al4V alloy (A) substrates by potentiostatic anodization (25 V - 90 min) in Simulated Body Fluid Solution (SBF) modified electrolyte kept at 10 and 40 C. Thermal profile investigation was performed by thermogravimetry (TGA) and Di erential Scanning Calorimetry (DSC), being defined the phase transition temperatures for annealing process (TT). Morphological and structural parameters were evaluated by Field Emission Scanning Electron Microscopy (FESEM), X-Ray Diraction (XRD), contact angle (CA) and nanoindentation. The results showed that self-organized nanotubular matrices were grown under all synthesis conditions. Electrolyte temperature was related to an increase in the nanotube inner diameter (Di) and alteration of wettability. The efect of TT was related with TiNTs collapse, becoming more evident with increasing annealing temperature. The nanoindentation analyses revealed that both the electrolyte and TT temperature have small efects on coatings hardness and elasticity modulus. In summary, this study showed that 40 C of synthesis conditions (with TT for substrate A samples) can significantly modify TiNTs properties, related to better coatings performance as biomaterial. In order to develop implants with resistance to bacterial activity, this work also presents a study of the modification of the best TiNT synthesis conditions using them as cefazolin sodium reservoir, covered with Chitosan (CH) and carboxymethylcellulose (CM) for control the drug release kinetics. Data from drug release assay showed that polymer covering can significantly reduce release rate. In addition, the disc-difusion test showed a high bacteriostatic profile from all samples. The hemolytic activity assay showed that samples have low hemolysis percentage, except for two conditions. It can be highlighted that samples that had obtained the best results were those that received the CM polymer coating. In summary, both the surface and polymeric coverage properties were important parameters to be considered in titanium-based biomaterials design.